A pedra do reino: romance epopeico audiovisual - personagens e figurinos - Oliveira, Mirella Pereira Diniz Luiggi (2010)
The main concern of this research is to understand in which way the present elements in the costume in a television scene perform the characterization of the presence mode of the narrative actants. In parallel, the research evaluates, by its elements, how the enunciator conveys to the public what it knows, can, does and feels a character and the context that it lives; the ways in which the dressed body makes be, does, knows, can and makes feel the actants in scene, the narrative whole and the present arrangements present in the clothing and the body to develop itself in the visibility and identity construction axis of the actants. It has been selected as a study object the television miniseries A Pedra do Reino having as main focus the construction of sense of the protagonist and the operator subject of the central action of the narrative, Pedro Dinis Quaderna; of the characters Clemente e Samuel, that act as modalizer subjects and that approach the national and political and social conflicts of the time; and the characters Dona Margarida and Maria Safira, members of a love triangle with Quaderna. With this corpus it has been tested and comproves in this dissertation that the costume represents not only a secondary choice or an ornament, but one of the pullars in the enunciator construction and its style, which is turned in its organization to the enunciater, allowing it the apprehension and the intelligibility of the meaning that is taken to construction. This development had as theoretical and methodological framework of the socio-semiotics in the treatments of the schemes of visibility of these actants whose costumes are the regent of their presence modes in the narrative plot, qualifying them by the different distinct media languages in syncretic articulation, that our study must describe and analyze. It has been evidenced that the investments in costumes that are more and more expressive in Brazilian television attest to the TV search in narrative productions of higher aesthetic quality that we have pointed, is not without consequence in the public formation. A Pedra no Reino as audiovisual experiment proposes an stimulation in the breeding of new aesthetic patterns